Within-sport specialisation and entry age as predictors of success among age group swimmers - Staub, I.; Zinner, C.; Bieder, A.; Vogt, T. (European Journal of Sport Science, 2020)
Early specialisation versus early diversification in long-term athlete development remains controversial. Although several parameters of sport specialisation have already been explored, this study investigates within-sport specialisation in the careers of young swimmers. In this cohort study, the number of strokes, events and distance categories during childhood and adolescence, as well as entry age were analysed to find potential correlations with success at age 18. Also, national team members were compared to non-members within this cohort. The number of events, strokes or distance categories at a younger age showed a moderate correlation to the best FINA point score at the age of 18, i.e. the greater the diversification, the greater the performance at age 18. The number of events, strokes or distance categories however, showed a stronger correlation when comparing national team members with the non-members. Most of the observed athletes were more likely to have high FINA points at 18 if they had been listed in the top 100 at 11 years of age. Entry age had a strong negative correlation with the FINA point score at 18, i.e. the younger the athlete when entering the top 100, the higher the FINA point score at 18. When national team members were compared to non-national team members, early age of entry into the top 100 showed a greater impact on the national team members. However, being listed in more than one stroke as a child correlates well with success at age 18.